2023
DOI: 10.1039/d2re00403h
|View full text |Cite
|
Sign up to set email alerts
|

One-pot cascade reactions for the synthesis of dinitroalkanes in aqueous buffer

Abstract: Dinitroalkanes are powerful synthetic building blocks because of the versatility of the 1,3-dinitro motif. Here, we show that dinitroalkanes can be synthesized from aliphatic aldehydes in a three-step cascade reaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…To this end, we recently showed that bio-aldehydes, generated with alcohol oxidase, can undergo a subsequent 3-step organocatalytic cascade to deliver good yields of 1,3-dinitroalkanes in single-flask conditions. 70 We have extended this methodology to include Pictet-Spengler annulation products from either bacterial or yeast-produced bioaldehydes. 71…”
Section: Biocompatible Upgradingmentioning
confidence: 99%
“…To this end, we recently showed that bio-aldehydes, generated with alcohol oxidase, can undergo a subsequent 3-step organocatalytic cascade to deliver good yields of 1,3-dinitroalkanes in single-flask conditions. 70 We have extended this methodology to include Pictet-Spengler annulation products from either bacterial or yeast-produced bioaldehydes. 71…”
Section: Biocompatible Upgradingmentioning
confidence: 99%
“…15,16 Recently, we extended this idea by coupling biocatalysed alcohol oxidation to a three-step Henry-dehydration-Michael cascade to deliver 1,3-dinitroalkanes. 17 Despite this recent progress, there are a dearth of reactions and guiding principles to adapt synthetic transformations to biocompatible conditions.…”
Section: Introductionmentioning
confidence: 99%
“…revealed that tyramine is a more effective organocatalyst than lysine for biocompatible aldol condensations [17] . We have also expanded the scope of biocompatible reactions by coupling biocatalysed alcohol oxidation to a three‐step Henry‐dehydration‐Michael cascade to deliver 1,3‐dinitroalkanes [18] . Nevertheless, despite this recent progress, there are a dearth of reactions and guiding principles to adapt synthetic transformations to biocompatible conditions.…”
Section: Introductionmentioning
confidence: 99%